Acute presentation of brachial plexus schwannoma secondary to infarction. Issue 3 (June 2015) - Sidani, Charif; Saraf-Lavi, Efrat; Lyapichev, Kirill A; Nadji, Mehrdad; Levi, Allan D
Schwannomas of the brachial plexus are rare and typically present as slowly growing masses. We describe a case of a 37-year-old female who presented with acute onset of severe left upper extremity pain. Magnetic resonance imaging (MRI) showed a 2.3 × 2.1 cm peripherally enhancing centrally cystic lesion in the left axilla, along the cords of the left brachial plexus, with significant surrounding edema and enhancement. The mass was surgically removed. Pathology was consistent with a schwannoma with infarction. The pain completely resolved immediately after surgery.